BERWAWASAN LINGKUNGAN DI INDONESIA: STUDI PERBANDINGAN KOTA METROPOLITAN DAN NON METROPOLITAN - Junaedi, M.F. Shellyana (Journal of Indonesian Economy and Business, 2006)
This study examined the model development causal that can predict the greenconsumer behavior on organic food as green product. This study tested the influenceof values orientation on environmental consciousness. This study also explained theeffect of ecological knowledge, ecological affect, premium price and environmentconsciousness on green purchase intention. The role of domicile area as moderatingvariables on the causal model development. The analysis of 723 respondents all ofthose are people who influence and purchase their daily food. The result, based onpath analysis using multi group structural equation modeling, indicated that themodel tested had an acceptable fit. The idea implied in this research will be muchhelp in resolving problem and decision making, connected to reinforce the greenJurnal Ekonomi dan Bisnis Indonesia, Vol 21 No.4 Tahun 2006purchasing.Keywords: green consumer behavior, organic food, domicile area